Answer:
guessed through it and made a 100 out of 150 pretty easy dude ( i'm only 14 so you can imagine how easy it is )
Step-by-step explanation:
Answer:
240
Step-by-step explanation:
2 is 1 + 1 so 120 + 120 must be the equivalent of 2.
The third dot is my answer. But don't take it for granted. Try it yourself and see what you come out with!
ANSWER
![d = - ab + c](https://tex.z-dn.net/?f=d%20%3D%20%20-%20ab%20%2B%20c)
EXPLANATION
The given expression is
![ab = c - d](https://tex.z-dn.net/?f=ab%20%3D%20c%20-%20d)
To find an expression for d in terms of a, b, and c, means we want to make d the subject of the relation.
This means that, we need to isolate d on one side of the equation while all other terms are on the other side.
We subtract from both sides of the equation to obtain,
![ab - c = - d](https://tex.z-dn.net/?f=ab%20-%20c%20%3D%20-%20d)
We now divide through by -1, to get,
![- ab + c = d](https://tex.z-dn.net/?f=%20-%20ab%20%20%2B%20%20c%20%3D%20d)
Or
![d = - ab + c](https://tex.z-dn.net/?f=%20d%20%3D%20-%20ab%20%20%2B%20%20c%20)
The topic is change of subject
Answer:
it is the first one
y=\sqrt{2x-6-1}
if i can get brainliest that would be great